The Ways of Isolating Neoantigen-Specific T Cells - Li, Qing; Ding, Zhen-Yu (Frontiers in Oncology, 2020)
Immunotherapy has revolutionized the standard of care for a range of malignancies. Accumulating evidence suggests that the success of immunotherapy is likely attributable to neoantigen-specific T cells. Thus, adoptive cell therapy with these neoantigen-specific T cells is highly promising. This strategy has proved to successfully elicit tumor regression or even complete remission in metastatic cancer patients. However, a fundamental challenge is to effectively identify and isolate neoantigen-specific T cells or their T cell receptors (TCRs), either from tumor infiltrating lymphocytes (TILs) or peripheral blood lymphocytes (PBLs), and many methods have been developed to this end. In this review, we focus on the current proposed strategies for identifying and isolating neoantigen-specific T cells.